Choosing to Live, Choosing to Dream, Choosing to Survive: War and Peace in Ukraine - Penna, Carla; Dibrova, Daria (Sens public, 2024)
A letter from Daria Dibrova, a young schoolteacher confronted with war in Odessa, followed by a reading of her letter in the light of Ukrainian history and the clinic of war trauma.